Introducing a common currency towards ASEAN economic integration. - Chen, Jeremy Xinheng. (2008)
The paper seeks to justify the implementation of a common currency in ASEAN,particularly ASEAN-5 through intensive research and analysis on issues pertaining to economic integration of ASEAN.